The MASP Family of Trypanosoma cruzi: Changes in Gene Expression and Antigenic Profile during the Acute Phase of Experimental Infection - dos Santos, Sara Lopes; Freitas, Leandro Martins; Lobo, Francisco Pereira; Rodrigues-Luiz, Gabriela Flávia; Mendes, Tiago Antônio de Oliveira; Oliveira, Anny Carolline Silva; Andrade, Luciana Oliveira; Chiari, Égler; Gazzinelli, Ricardo Tostes; Teixeira, Santuza Maria Ribeiro; Fujiwara, Ricardo Toshio; Bartholomeu, Daniella Castanheira (PLOS Neglected Tropical Diseases, 2012)
Author Summary The parasite Trypanosoma cruzi is the etiologic agent of Chagas disease, a neglected tropical disease. A major finding of the T. cruzi genome project was the discovery of a multigene family that encodes mucin-associated surface proteins (MASP), a highly polymorphic family expressed at the surface of infective forms of the parasite. We speculate that MASP may contribute to the ability of T. cruzi to infect several host cells and/or participate in host immune evasion mechanisms. To begin investigating this hypothesis, we analyzed the MASP expression profile in trypomastigotes derived from different host cells and in bloodstream parasites after sequential passages in mice. We also investigated the MASP antigenic profile in acutely infected mice. We observed more pronounced MASP expression changes by comparing bloodstream and tissueculture trypomastigotes and between bloodstream forms from sequential passages in infected mice. We also found that MASP peptides could trigger different IgG and IgM antibody responses and that the antibody level against a given peptide may vary after sequential passages in mice. We speculate that changes in the large repertoire of MASP antigenic peptides during the course of an infection may contribute to the evasion of host immune responses during the acute phase of Chagas disease.